PARP inhibitors in metastatic prostate cancer - Taylor, Amy K.; Kosoff, David; Emamekhoo, Hamid; Lang, Joshua M.; Kyriakopoulos, Christos E. (Frontiers in Oncology, 2023)
Poly-ADP ribose polymerase inhibitors (PARPi) are an emerging therapeutic option for the treatment of prostate cancer. Their primary mechanism of action is via induction of synthetic lethality in cells with underlying deficiencies in homologous recombination repair (HRR). In men with metastatic castrate-resistant prostate cancer (mCRPC) and select HRR pathway alterations, PARPi treatment has been shown to induce objective tumor responses as well as improve progression free and overall survival. Presently, there are two PARPi, olaparib and rucaparib, that are FDA approved in the treatment of mCRPC. Ongoing research is focused on identifying which HRR alterations are best suited to predict response to PARPi so that these therapies can be most effectively utilized in the clinic. While resistance to PARPi remains a concern, combination therapies may represent a mechanism to overcome or delay resistance.